Research and Simulation of Improved Smith Prediction Algorithm Based on PLC - Wang, Dongxue; Ren, Juan; Zhang, Jie; Yu, Xiaoqing; Zheng, Liangjun (International Journal of Computer Science and Information Technology, 2024)
Aiming at the problem of excessive overshoot caused by large delay in temperature control process, based on the research of Smith predictive control algorithm, an improved gain adaptive Smith predictive control scheme is proposed, which can track the change of gain in real time. The simulation program is written based on TIA Botu and configuration software, and the operation results show that the improved scheme improves the lag effect and the adaptability to the model, and it still has good control quality after the parameter changes.